Clinical Trials of Probiotic Strains in Selected Disease Entities - Ruth Dudek-Wicher; Adam Junka; Justyna Paleczny; Marzenna Bartoszewicz (International Journal of Microbiology)
Probiotics are live microorganisms which when administered in adequate amounts confer a health benefit on the host. Although their mechanism of action is not clearly explained, it is known that they positively modulate the immune system, which leads to immunity potentiation. A number of studies prove that probiotics strengthen cognitive functions, reduce anxiety, and regulate the lipid metabolism in the human body. Probiotics used in humans are most often of the Lactobacillus and Bifidobacterium species. However, as more research is conducted, new species with beneficial, probiotic properties are being discovered. This paper provides a review of available information about the influence of probiotics on human health. It summarizes the current knowledge on the mechanism of action of probiotics as well as clinical trial results proving their efficacy in allergic, neurodegenerative, and cardiac diseases. This review also discusses the data concerning the safety of probiotics in clinical treatment.